Investigation of amino acids’ levels in the vitreous body of experimental animals in regmatogenic retinal detachment - Levytska, H.; Levytskyi, I.; Savytskyi, I.; Zaiats, L.; Sarakhan, L. (Journal of Education, Health and Sport, 2021)
The article presents the results of studying the levels of amino acids in the vitreous body of rats with rhegmatogenous retinal detachment at different stages of modeling the pathology (on the 3rd, 5th and 7th day). In animals with modeling RRD, was observed a significant increase in the level of alanine, aspartate, glycine, glutamic acid compared with rats of conditionally intact group; maximum changes in indicators were observed on the 7th day of the study. The obtained data are explained by significant neurochemical changes of the glutamatergic system of the neural retina, which cause excitotoxicity (as a result of massive release of neuronal glutamate) and structural changes. In the study of the level of valine, histidine, tyrosine, phenylalanine and methionine, it was found that these amino acids are not involved in the pathogenesis of RRD, so their level does not change. The obtained experimental data deepen the existing pathophysiological data on the pathogenetic links of rhegmatogenous retinal detachment in the early stages of its progression, which is important for practical ophthalmology to develop effective pharmacotherapy of this disease.